Thermal evaluation and biological control of cooling towers - Trujillo, Hernán; Colina, Javier; Sánchez, Jorge (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The cooling water system of the Amuay refinery consists of two induced draft and cross flow cooling water towers, seven pumps and four supply pipes and their returns. This system supplies cooling water to the hydrotreatment complex, to the pipestill N° 5 and to the surface condensers of the power plant turbogenerators. This cooling water system showed constraints in the tower's cooling capacity to meet the design conditions, due mainly to a biological growth inside the towers, also increasing the need for cleaning more frequently the surface condensers of the power plant turbogenerators, indicating that the microbiological control was not suitable. In this study a thermal evaluation was performed to the towers, before and after the application of a biological control program by means of biocides and biodispersants, to decrease the growth of microorganisms. The towers were operating at 83% of their design cooling capacity, mainly because of the growth of algae inside them. After implementing the microbiological program, the cooling efficiency increased to 91%. Likewise, the heat transfer in the surface condensers of the power plant turbogenerators also increased.